Tunable Add–Drop Filter With Hollow Bottlelike Microresonators - Zhong-Hao Zhou; Yuan Chen; Zhen Shen; Chang-Ling Zou; Guang-Can Guo; Chun-Hua Dong (IEEE Photonics Journal, 2018)
In this paper, we report the narrow-band tunable add–drop filter (ADF) based on the hollow bottlelike microresonator with two taper fibers corresponding to the bus and drop waveguides. We theoretically and experimentally study the relationship between the drop efficiency and the coupling losses of the bus waveguide resonator and the add–drop waveguide resonator. The tuning range of the ADF of 270 GHz ( $\sim$ 2.2 nm) and the drop efficiency of approximately $76%$ have been realized. By such ultranarrow-band filter based on high Q microresonators, a laser beam with specified frequency is filtrated from the background laser with frequency interval of 86 MHz. This tunable ultranarrow-band ADF has potential for applications in the quantum optomechanical experiments and narrow-band quantum photon sources by filtrating the weak signals from pump and noise backgrounds.